Lexical Availability in CLIL: Differences in Language of Instruction - Geoghegan, Leah (International Journal of English Studies, 2024)
Within the context of Content and Language Integrated Learning (CLIL), vocabulary acquisition is of central importance. However, while CLIL is increasingly being implemented throughout Spain, there remains a clear preference, both in practice and research, for using English over other languages such as French. This study thus investigates the token production of Spanish students taking both English and French CLIL classes by means of a lexical availability task. It aims to determine if there are quantitative differences between the learners’ language level and token production in English and French, and whether these differences exist across grades. Results indicate that learners have higher proficiency and produce more words in English, and that CLIL instruction has a clear impact on learners’ production across grades. The results are of key interest to multilingual CLIL educators seeking to make the most of vocabulary gains in multiple languages.